Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1562/0031-8655(2003)0770510loflis2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Lengthening of Fluorescence Lifetimes in Self-organized Metal-Organic Assemblies ¶

Abstract: Resonance energy transfer from tris(2,29-bipyridyl)ruthenium (II) ([Ru(bpy) 3 ] 2+ ) to nile blue A is demonstrated in aqueous solution in the presence of sodium dodecyl sulfate (SDS). At SDS concentrations below the critical micelle concentration, aggregates that permit energy transfer between these dyes at optically dilute (10 lM) concentrations with nearly 100% efficiency are formed. The disparity between the lifetimes of the donor and acceptor results in the lengthening of the photoluminescence lifetime of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This was originally recognized in FRET-based experiments using QD donors and molecular fluorescent acceptors. Interestingly, CdSe exhibits characteristics of being an exceptional singlet or triplet energy donor, depending upon the molecular species in which it is partnered. This is akin to MLCT-based photosensitizers such as [Ru­(bpy) 3 ] 2+ . The admixture of singlet/triplet character enables observations of both efficient FRET and TTET from the MLCT excited state. ,, ,, This suggests that the photophysical processes occurring in QDs echo those in molecular-based photosensitizers, and they can be envisioned in the same manner. For example, it was recently shown that CdSe QDs were able to triplet sensitize [2 + 2] cycloaddition chemistry in a variety of surface-bound organic substrates .…”
Section: Outlook and Potential Research Directionsmentioning
confidence: 99%
“…This was originally recognized in FRET-based experiments using QD donors and molecular fluorescent acceptors. Interestingly, CdSe exhibits characteristics of being an exceptional singlet or triplet energy donor, depending upon the molecular species in which it is partnered. This is akin to MLCT-based photosensitizers such as [Ru­(bpy) 3 ] 2+ . The admixture of singlet/triplet character enables observations of both efficient FRET and TTET from the MLCT excited state. ,, ,, This suggests that the photophysical processes occurring in QDs echo those in molecular-based photosensitizers, and they can be envisioned in the same manner. For example, it was recently shown that CdSe QDs were able to triplet sensitize [2 + 2] cycloaddition chemistry in a variety of surface-bound organic substrates .…”
Section: Outlook and Potential Research Directionsmentioning
confidence: 99%
“…Amanda Morris and her group at Virginia Tech in Blacksburg, VA, carried out a detailed study of Förster-type resonance energy transfer (FRET) occurring between identical Ru II MLCT chromophores, which were postsynthetically appended in the metal–organic framework UiO-67 . It should be noted that FRET has been shown to be operative in Ru II MLCT molecules, serving as either donors or acceptors for various organic chromophores in solution. However, this investigation by Morris and colleagues quantitatively suggests that the dynamic self-quenching of the observed charge-transfer photoluminescence results exclusively from FRET in two and three dimensions. An important implication of this work is that FRET may be more widespread in materials incorporating MLCT excited states than originally thought, and this may be especially true in materials containing high concentrations of these chromophores in close proximity.…”
mentioning
confidence: 99%